Effects of Various Semen Extenders on the Hatching Characteristics of Japanese Quail - F Raziq; MT Khan; A Ullah; U Farooq; R Akhtar; B Siddique; G Abbas; F Ali; S Aslam; H Khaliq; H Ali; MF Khalid; et al. (Brazilian Journal of Poultry Science)
ABSTRACT Reproductive efficiency is a cornerstone of success in poultry production, particularly in species such as the Japanese quail (Coturnix coturnix japonica), which are valued for their high productivity and adaptability. Semen extenders have been evaluated for their efficacy in preserving sperm quality and improving reproductive outcomes. This study assessed the effects of different semen extenders on the reproductive performance of Japanese quail, focusing on key parameters such as fertility, hatchability, and semen quality. Over a period of twenty-eight days, a total of 300 adult female breeder quails (5 to 6 weeks of age) with an average weight of 200 ± 8 g were divided into four experimental groups, under a completely randomized design. The treatment groups included T1 (proctodeal gland foam), T2 (quail egg albumen), T3 (Shit’s extenders), and T4 (control group with undiluted semen). Each group comprised five replicates with 15 birds per replicate. Additionally, 75 male breeder quails with an average weight of 170 ± 7 g were housed separately for semen collection and analysis. The results showed that birds in the T1 group, treated with proctodeal gland foam as a semen extender, exhibited the highest fertility and hatchability rates. This group also displayed improved semen quality, with increased sperm motility and a higher percentage of live sperm count. These findings suggest that proctodeal gland foam is an effective semen extender for enhancing reproductive outcomes in Japanese quails.